The Effect of Scientific Approach on Early Reading Ability in Early Childhood Group A at Aidil Fitri 2 Kindergarten Palembang - Sabrina, Ully; Astuti, Mardiah; Oktamarina, Lidia; Febriyanti, Febriyanti; Sartika, Indah Dwi; Atika, Nyimas (Al-Mudarris, 2024)
This research provides a background for an image that students in early reading have not developed optimally. With the title of the research on "The Effect of Scientific Approach on Early Reading Ability in Early Childhood Group A at Kindergarten Aidil Fitri 2 Palembang". The purpose of this study is to find out whether there is an influence of the Scientific Approach on Early Reading Ability in Early Childhood Group A at Aidil Fitri 2 Kindergarten Palembang. This type of research is an empirical discovery expos that are carried out systematically, the researcher does not control the independent variables. The number of samples amounted to 16 from educators, parents of students and students at Aidil Fitri 2 Kindergarten Palembang. Data collection techniques in the study used observation, questionnaires and documentation. The data analysis techniques used in this study used validity tests, reliability tests, normality tests and hypothesis tests. The results of the study showed that the results of the t-test of the t-value of the calculation (6,015) > the t-value of the table (1,745) with a sig value of 0.001 meant that there was an influence of the Scientific Approach (X) on the ability of Children's Early Reading (Y) at Aidil Fitri 2 Kindergarten Palembang. With the hypothesis value of Ho rejected and Ha accepted, it means that there is a significant influence of variable X on variable Y. With an R Squara value of 0.567 (56.7%). Therefore, it can be concluded that there is a significant influence between the Scientific Approach on Early Reading Ability in Early Childhood Group A at Aidil Fitri 2 Kindergarten Palembang with an actual percentage value of 56.7%, this is stated that the scientific approach has a strong influence on early reading ability in early childhood group A at Aidil Fitri 2 Kindergarten Palembang.